Aeronaves asombrosos - Simon, Seymour; Bell, Elizabeth S. (San Francisco : Chronicle Books, 2006)
Provides an easy-to-read overview of the history of aircraft.
"Nivel 2"--Cover.
Accelerated Reader
Keywords: Airplanes -- History -- Juvenile literature; Aviones -- Historia -- Literatura juvenil